2022
DOI: 10.3389/fpsyg.2022.901031
|View full text |Cite
|
Sign up to set email alerts
|

Nothingness Is All There Is: An Exploration of Objectless Awareness During Sleep

Abstract: Recent years have seen a heightened focus on the study of minimal forms of awareness during sleep to advance the study of consciousness and understand what makes a state conscious. This focus draws on an increased interest in anecdotical descriptions made by classic Indian philosophical traditions about unusual forms of awareness during sleep. For instance, in the so-called state of witnessing-sleep or luminosity sleep, one is said to reach a state that goes beyond ordinary dreaming and abide in a state of jus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 71 publications
0
14
0
Order By: Relevance
“…Here I claim that such states of 'void' or 'clear light dreams' could be understood as per the technical notion of lucidity if such states are regarded as perceptual states; states in which I'm aware that I'm in a state that lacks a dream environment. This claim would be supported by recent phenomenological reports of those experiences collected by empirical work (see Alcaraz-Sánchez 2021;Alcaraz-Sánchez et al 2022). Those reports point to an experience that in some cases seems to involve a certain 'distinct' object of awareness, like the awareness of one's location in the 'void' or one's self-experience in such a state (ibid).…”
Section: Imageless Lucid Dreaming and Experiences Of The Voidmentioning
confidence: 82%
See 1 more Smart Citation
“…Here I claim that such states of 'void' or 'clear light dreams' could be understood as per the technical notion of lucidity if such states are regarded as perceptual states; states in which I'm aware that I'm in a state that lacks a dream environment. This claim would be supported by recent phenomenological reports of those experiences collected by empirical work (see Alcaraz-Sánchez 2021;Alcaraz-Sánchez et al 2022). Those reports point to an experience that in some cases seems to involve a certain 'distinct' object of awareness, like the awareness of one's location in the 'void' or one's self-experience in such a state (ibid).…”
Section: Imageless Lucid Dreaming and Experiences Of The Voidmentioning
confidence: 82%
“…For now, I'll focus on examining the state of the clear light sleep characterised as a state of non-duality, a state that lacks the subjectother distinction of ordinary conscious states and that is taken by Tibetan Buddhist traditions to be an objectless state; it's said to lack an object-directed awareness inasmuch as it lacks a distinctive object of awareness from the mind itself (cf. Alcaraz-Sánchez 2021; Alcaraz-Sánchez et al 2022).…”
Section: Lucid Dreamless Sleep and The Clear Light Sleepmentioning
confidence: 99%
“…Phenomenological methods have been used in cognitive science reports as a single source of information. Thus far, several studies have shown that the description of lived experience can be accurate and also very detailed, allowing for a better understanding of phenomena such as meditative states ( Berkovich-Ohana et al, 2013 ; Nave et al, 2021 ), awareness in sleep ( Alcaraz-Sánchez et al, 2022 ), temporal variation of emotional state ( Depraz et al, 2017 ), and visual attention ( Lachaux et al, 2000 ), among others (for a review see Berkovich-Ohana et al, 2020 ).…”
Section: Methodological Progression Based On the 5e Approach For A Co...mentioning
confidence: 99%
“…Since its incorporation into the field of cognitive science, phenomenology has exhibited accuracy and high utility in understanding phenomena such as meditative states ( Silva-Mack et al, 2018 ; Nave et al, 2021 ), contemplative training ( Przyrembel and Singer, 2018 ), epilepsy ( Le Van Quyen and Petitmengin, 2002 ), fibromyalgia ( Valenzuela-Moguillansky, 2013 ), and chronic pain ( Smrdu, 2022 ). In addition, analysis of subjective experience captures very subtle descriptions of embodied experiential microdynamics, such as approach and avoidance behaviors ( Baquedano and Fabar, 2017 ), exploration of awareness during sleep ( Alcaraz-Sánchez et al, 2022 ), adjustments of attention ( Lachaux et al, 2000 ), variation of emotional state ( Depraz et al, 2017 ), and movement intention ( Jo et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%